Jarimatika method of daily prayer: Does it affect children’s spiritual intelligence? - Hijriati, Hijriati; Hayati, Zikra; Karnisah, Karnisah (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
Memorizing daily prayers has become a daily lesson in kindergarten. However, they find it challenging to memorize daily prayers without knowing the meaning, not understanding what is memorized, and they forget if not repeated and practiced by the teacher. This study aims to determine whether there is an influence between memorizing daily prayers by using the jarimatika method on children's spiritual intelligence at Malahayati Kindergarten, South Aceh. The jarimatika method of daily prayers relies on knuckles in memorizing daily prayers. Spiritual intelligence includes the development of awareness to build relationships with others in an ethical, moral and humane manner. This study used an experimental method with the number of samples taken in this study consisting of 11 children aged 5-6 years as the experimental class. The data analysis technique used is the t-test, hypothesis and normality test. The results of data analysis obtained tcount> ttable;17.33>1.812. Ha is accepted, and Ho is rejected. Therefore, the jarimatika method increases children's memorization of daily prayers and affects their spiritual intelligence.